Self-Concept Siswa Pada Pemecahan Masalah di SD - Muhammad Fadlullah; Feny Rita Fiantika; Prayogo (Universitas Muhammadiyah Surabaya, 2026)
Solving mathematical problems calls for some difficult cognitive abilities. Deep awareness of the problem, proper strategy development, thorough implementation of the plan, validation of the solution to guarantee accuracy, and result evaluation help to develop future talents by means of this procedure. For elementary school pupils to overcome obstacles in studying mathematics, this talent is quite crucial. This paper reviews elements of elementary school kids’ self-concept to investigate their capacity for problem-solving. Conducted at SDN Kebonagung 1 Sukodono with pupils of class V-A, this study applied a descriptive qualitative method. Data were gathered by means of student grades, observations, written assessments, questionnaires, and interviews. The studies revealed that ability to solve mathematical problems depends on self-concept. High self-concept pupils are more likely than others with modest or low self-concept to satisfy the four criteria of problem solving.